2010
DOI: 10.1111/j.1440-1770.2010.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary production and biomass of Cladocera in marginal lakes after the recovery of their hydrologic connectivity in a river–reservoir transition zone

Abstract: Secondary production and biomass of Cladoceran populations were studied in two marginal lakes whose connections to a tropical river were re-established after a prolonged drought period. This study investigates the process of the recovery of the cladoceran populations after the hydrologic reconnection with the river was established. It also compares the energetic dynamic of Cladoceran populations in two lakes, one with a wide and another with a narrow connection to the river. Samples were collected every 48 h f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
9
2
1
Order By: Relevance
“…The relationship of a larger river-lake connection to high cladoceran richness was observed by Panarelli et al (2010) in lakes adjacent to the Paranapanema River (São Paulo), in contrast to our observations for Taquari oxbow lakes. Nevertheless, these authors observed the highest richness and diversity associated with low organism density and extensive macrophyte colonisation, similar to the situation observed for Taquari oxbow lakes.…”
Section: Discussioncontrasting
confidence: 99%
“…The relationship of a larger river-lake connection to high cladoceran richness was observed by Panarelli et al (2010) in lakes adjacent to the Paranapanema River (São Paulo), in contrast to our observations for Taquari oxbow lakes. Nevertheless, these authors observed the highest richness and diversity associated with low organism density and extensive macrophyte colonisation, similar to the situation observed for Taquari oxbow lakes.…”
Section: Discussioncontrasting
confidence: 99%
“…The impacted station of Lake Batata showed intermediate values, because this station is mesotrophic due to bauxite tailings. A similar pattern was observed by Panarelli et al (2010), comparing two marginal lakes of the Paranapanema River in São Paulo (Brazil). Conversely, Rietzler et al (2004) found much higher values in the eutrophic Salto Grande Reservoir in São Paulo (Brazil).…”
Section: Discussionsupporting
confidence: 82%
“…This relationship between the increasing of microcrustacean productivity with the increasing of trophic state (Tab. 5) recurs in other Brazilian aquatic ecosystems.All studies in Brazilian lakes and reservoirs used the biomass increment method of Winberg et al (1965) and the present study applied the method of Hart (1987), and both direct (Maia-Barbosa, 2000;Melão et al, 2004 and2006;Rietzler et al, 2004;Santos-Wisniewski and Rocha, 2007) and indirect (Panarelli et al, 2010;Santos et al, 2010) methods were employed to estimate the zooplankton biomass. In spite of these methodological differences, the values of secondary productivity were compatible with each other.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…On the other hand, reduced water volume causes instability of aquatic populations and influences diversity of Cladocera (Panarelli et al, 2010). This may be in agreement with the theory proposed by Naselli-Flores et al (2003), who suggest a tendency of nonequilibrium of the steady-state conditions in the phytoplanktonic community when one or more environmental factors are at the extreme of the range in which organisms can grow and when the change is either too abrupt or too complete and exceeds the homeostatic plateau of the assemblage.…”
Section: Discussionmentioning
confidence: 99%